(untitled) (Law Research Review Quarterly, 2026)
Land occupies a strategic position in the Indonesian agricultural legal system, in which the right to land ownership is reserved for Indonesian citizens (WNI) only, in accordance with Article 21 of the Basic Agrarian Law (UUPA). This provision poses a problem for WNI who are in mixed marriages. The reason for this is that the joint property system can lead to land ownership rights being regarded as mixed ownership and thus run the risk of passing into the hands of foreign nationals (WNA). This study analyzes the role of marriage contracts as a legal solution to protect the land ownership rights of WNI in mixed marriages. The study uses a legal-normative method with a legislative and conceptual approach. The results of the study show that Constitutional Court Decision No. 69/PUU-XIII/2015 recognizes prenuptial agreements concluded after marriage, allowing for retroactive separation of property. Furthermore, this protection is reinforced by Government Regulation No. 18 of 2021, Article 70, which states that Indonesian citizens married to foreigners can retain land rights based on a property division agreement. This is further reinforced by technical regulations issued by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, which provide legal certainty and administrative mechanisms for land ownership. Overall, marriage contracts serve as an important tool for protecting the constitutional rights of Indonesian citizens, preventing control of land by foreigners, and ensuring justice and legal certainty in mixed marriages.